2018
DOI: 10.1093/neuros/nyy445
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits After Elective Spine Surgery

Abstract: BACKGROUND Emergency department (ED) overuse is a costly and often neglected source of postdischarge resource utilization after spine surgery. Failing to investigate drivers of ED visits represents a missed opportunity to improve the value of care in spine patients. OBJECTIVE To identify the prevalence, drivers, and timing of ED visits following elective spine surgery. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“… 28 ED presentation and readmission after total knee and total hip arthroplasty have proven to be a high burden to the health care system and have prompted discussion about patient-centered interventions that can safely intervene and prevent those outcomes. 35 Our results suggest that patients with sustained opioid use after surgery require both monitoring and judicious intervention 26 to optimize their safety and lower the risk for ED visits and hospital admissions after index arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
“… 28 ED presentation and readmission after total knee and total hip arthroplasty have proven to be a high burden to the health care system and have prompted discussion about patient-centered interventions that can safely intervene and prevent those outcomes. 35 Our results suggest that patients with sustained opioid use after surgery require both monitoring and judicious intervention 26 to optimize their safety and lower the risk for ED visits and hospital admissions after index arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that postoperative ED visits in this population are typically related to pain and medical concerns. 27 Since many ED visits are avoidable following spine surgery, 28 interventions aimed at decreasing unnecessary ED visits may help reduce the overall cost of postoperative care for patients following ACDF. Apart from readmissions, the 3 largest contributors to postoperative spending were imaging, physical therapy, and medical supplies/devices (13.7% to 14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…lumbar) reported a 90-day ED visit rate of 9.4%, and independent risk factors were younger age, baseline opioid intake, chronic obstructive pulmonary disorder, and a larger number of surgically treated vertebral levels. 25 Patients with a 90-day ED visit also had a significantly lower 3-month EQ-5D score. 25 Another study by Jain et al focusing on primary lumbar fusion reported a 30-day ED visit rate of 12.8% with some similar predictors to our model, including Black race, ALIF, and ≥ 3 surgically treated levels.…”
Section: Fig 2 Nomogram Representing Prediction Model For 30-day Read...mentioning
confidence: 91%
“…25 Patients with a 90-day ED visit also had a significantly lower 3-month EQ-5D score. 25 Another study by Jain et al focusing on primary lumbar fusion reported a 30-day ED visit rate of 12.8% with some similar predictors to our model, including Black race, ALIF, and ≥ 3 surgically treated levels. 26 ALIF operations have been shown to be associated with increased rates of postoperative complications, readmissions, and hospital costs.…”
Section: Fig 2 Nomogram Representing Prediction Model For 30-day Read...mentioning
confidence: 91%